Implementing gold investment for Malaysian Employees Provident Fund (EPF) - Nurshuhaida Abdul Razak; Aisyah Abdul-Rahman; Salmy Edawaty Yaacob (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The Employees Provident Fund (EPF) was established under the Provident Fund Act 1991 (Act 452) which provides retirement benefits to its contributors under an efficient and trusted management appointed by the government. Both private and public sector employees are allowed to contribute; whereby EPF acts as a fund manager on behalf of the contributors and provides a guaranteed minimum dividend of 2.5 per cent per annum. Majority of EPF investments are of low risk financial instruments; and this is done as to ensure the contributors enjoy the minimum returns. As majority of EPF contributors are Muslims, two critical issues have risen, especially when EPF seems to be ignorant by not investing in shariah compliant instruments on top of its uncompetitive returns. As gold investment has so far shown to produce high long term investment return, we examined the suitability of introducing shariah compliant gold investment saving account as one of the EPF portfolio investment instruments. We suggested that EPF allocates around 15 per cent of its investment portfolio in shariah compliant gold account for the benefit of EPF contributors as to maintain their purchasing power after retirement. As gold hedges against inflation, investing in shariah– compliant gold investment account solves the dilemma of Muslim EPF contributors in non-permissible investment.